Determinants of consumers' supermarket selection: empirical evidence on East Malaysian shoppers' behavior / Oriah Akir, Normah Sidi and Senian Malie - Akir, Oriah; Sidi, Normah; Malie, Senian (2008)
This study was undertaken to ascertain the determinants that drive consumers to patronize a supermarket. In addition, the study also looked into stores' attributes that were most preferred and attracted consumers to frequently utilize those supermarkets. The relationship of consumers' religious orientation and consumers' shopping behavior types was also determined. A nonprobability sampling technique was applied to collect the data. The data was collected via mall intercepts with a structured questionnaire used to interview the consumers at six supermarkets under the jurisdiction of Dewan Bandaraya Kuching City North, Sarawak. A new mix cluster of shopper types emerged from the study, namely: demanding-practical shoppers, thoughtful innovative shoppers, while some are indifferent-confused shoppers. The results also indicated the existence of a relationship between the customers' religious orientation and their shopping behavior types. Essentially, the study revealed some similarities and differences from previous studies with respect to the determinants and store (supermarket) physical attributes most preferred by consumers when deciding on a supermarket. It also showed some similarities and differences in shoppers' behavior types. Therefore, understanding consumers' shopping behavior and what drives them to visit a supermarket, is of prior importance to both retail managers and marketers in order to guide them in developing and executing strategies to sustain consumers' loyalty. This is due to the fact that consumers' behavior may differ across nationality, cultures, regions and locations.